2018
DOI: 10.1186/s12870-018-1499-7
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic and ecophysiological responses of soybean (Glycine max L.) root nodules to Pb and hg stress

Abstract: BackgroundLead (Pb) and mercury (Hg) are persistent hazardous metals in industrially polluted soils which can be toxic in low quantities. Metal toxicity can cause changes at cellular and molecular level which should be studied for better understanding of tolerance mechanism in plants. Soybean (Glycine max L.) is an important oilseed crop of the world including India. Indian soils growing soybean are often contaminated by Pb and Hg. The aim of this study was to explore how soybean root nodule responds to Pb and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 72 publications
0
19
0
Order By: Relevance
“…From last two decades, numerous innovative methods such as protein detection using mass spectrometry, microarray technique, and the yeast two-hybrid system have been developed and used for large scale analysis of proteins, which involved in stress signaling and stress tolerance. Though several groups around the world have used the transcriptomics approach to investigate and to underpin expression level and patterns of different genes relating to PAs induced stress amelioration [115,116]; nonetheless, such analysis of mRNA levels has some limitations [117], such as the poor correlation between the expression patterns of mRNAs and their corresponding proteins [118]. Moreover, although the correlation between the expressions of mRNA and corresponding proteins has been identified [119] protein expression is also influenced or regulated at both translational and post-translational levels.…”
Section: Omics Approaches To Improve Polyamines Actions Towards Mementioning
confidence: 99%
See 1 more Smart Citation
“…From last two decades, numerous innovative methods such as protein detection using mass spectrometry, microarray technique, and the yeast two-hybrid system have been developed and used for large scale analysis of proteins, which involved in stress signaling and stress tolerance. Though several groups around the world have used the transcriptomics approach to investigate and to underpin expression level and patterns of different genes relating to PAs induced stress amelioration [115,116]; nonetheless, such analysis of mRNA levels has some limitations [117], such as the poor correlation between the expression patterns of mRNAs and their corresponding proteins [118]. Moreover, although the correlation between the expressions of mRNA and corresponding proteins has been identified [119] protein expression is also influenced or regulated at both translational and post-translational levels.…”
Section: Omics Approaches To Improve Polyamines Actions Towards Mementioning
confidence: 99%
“…Moreover, targeting these proteins can be useful in improving metal stress in non-tolerant plant species. Similarly, Baig et al [118] used proteomics approach and showed that Pb stress tolerance in soybean was associated with a high accumulation of thermospermine synthase ACAULIS5-like protein, this is encoded by ACAULIS5 ( ACL5 ) gene and converts Spd to thermospermidine [124].…”
Section: Omics Approaches To Improve Polyamines Actions Towards Mementioning
confidence: 99%
“…Soybean (Glycine max L.) is the most widely cultivated legume around the world due to its high protein and oil content (Singh et al 2008;Nisa et al 2016;Baig et al 2018). Its world production reached 338 million tons in the 2017/2018 harvest, with the United States, Brazil and Argentina being the main producers (FAO 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In Arabidopsis these transporters are localized in different membrane compartments: SOS1/ AtNHX7 on the plasma membrane, AtNHX5/6 on endosomes, and AtNHX1-4 on the tonoplast (Chanroi et al, 2012). The mutations in the gene NHX7/SOS1 cause oversensitivity to salt due to disrupted efflux of sodium (Sze et al, 2004;Pardo et al, 2006, Bassil andBlumwald, 2014;Sandhu et al, 2018). Upregulation of NHX7/SOS1 was shown to be associated with salt tolerance in Medicago species (Liu et al, 2015;Sandhu et al, 2017).…”
Section: In Silico Gene Expression Analysis Of Potassium/sodium Ion Tmentioning
confidence: 99%